Multiplicidade de padrões voluntários de sustentabilidade na exportação global de café - Beltrame, Nicole (Universidade Federal de São Carlos, 2022)
In the global dynamics of coffee exports, the Sustainability Standards (SS) have been created since 1980, aiming at assigning criteria and requirements to be met by agents who pass through social, environmental, governance, equity, etc. However, adherence to the SS incurs costs so that agents are in compliance and can access specific markets and maintain the established commercial relationships. Furthermore, the increasing number of new standards worldwide created duplicity and overlapping criteria adopted by these standards and intensified competition between them. This effect is called the Multiplicity of Sustainability Standards. The objective of this work is to analyze the landscape of the multiplicity in the coffee market, considering the most significant coffee exporting countries in the world (Brazil, Vietnam, Colombia, Honduras and India) from the analysis of overlap (SOI) and competition (HIS) of standards and also the combination between them. For this, eight SS have been selected: Common Code for the Coffee Community (4C), Coffee Sustainability Reference Code, Rainforest Alliance, FairTrade, FairTrade Small Producers, UNCTAD, Small Producers Symbol and IFOAM. For each sustainability standard, requirements are assigned to be met for its adherence, including environmental, social, human and women's rights requirements and best practices for land and water use, among others. These requirements allow us to calculate the indices mentioned above. From this, it is possible to analyze the dynamics between sustainability standards, their competitive strength and the degree of overlap compared to other standards.
Multiplicity of voluntary sustainability standards in global coffee exports
Keywords: Padrões de sustentabilidade; Café; Exportação; Multiplicidade de padrões; Sustainability standards; Coffee; Export; Multiplicity of standard; CIENCIAS SOCIAIS APLICADAS::ECONOMIA